Maternal Age, Pregnancy Spacing, and Nutritional Status Associated with Preeclampsia: Usia Ibu, Jarak Antara Kehamilan, dan Status Gizi yang Berkaitan dengan Preeklampsia - Lailiyah, Yunike; Azizah, Nurul; Cholifah, Cholifah; Purwanti, Yanik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Preeclampsia remains a major complication of pregnancy, significantly contributing to maternal and perinatal morbidity and mortality worldwide. Specific Background: In Indonesia, the prevalence of preeclampsia continues to rise, with 587 cases reported in Sidoarjo Regency in 2022. Age, pregnancy spacing, and maternal nutritional status are suspected to be key determinants. Knowledge Gap: Although various studies have explored risk factors for preeclampsia, limited evidence links maternal age, pregnancy spacing, and nutritional status in a specific regional context. Aims: This study aims to examine the relationship between maternal age, pregnancy spacing, and nutritional status with the incidence of preeclampsia among pregnant women in Sidoarjo. Results: Among 96 respondents, 52.1% were at risk maternal age, 61.5% had risky pregnancy spacing, and 58.3% had abnormal nutritional status. Chi-square analysis revealed significant associations: maternal age with preeclampsia (p=0.001; OR=5.460), pregnancy spacing (p=0.000; OR=0.019), and nutritional status (p=0.000; OR=0.139). Novelty: This research provides region-specific evidence of maternal factors influencing preeclampsia in Sidoarjo. Implications: Strengthening antenatal care, focusing on maternal nutrition, reproductive age, and pregnancy planning, is essential to reduce preeclampsia prevalence. Highlights: Maternal age is strongly associated with preeclampsia risk. Pregnancy spacing less than 2 years or more than 5 years increases preeclampsia likelihood. Abnormal maternal nutritional status significantly correlates with preeclampsia. Keywords: Preeclampsia, Maternal Age, Pregnancy Spacing, Nutritional Status, Pregnant Women